Wokół triady ciało - zdrowie - media (analizy i refleksje) = Around the triad body - health - media (analyses and reflections) - Porycka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Postmodern era, the Internet, anorexia, diseases of affluence - is there a connection between these phenomena? Fast development of the Internet and the rise of social media have made the access to many dangers unlimited. Nowadays almost all young people have access to the Internet which is, so to speak, always with them, through various portable devices. One of these dangers is the development of virtual societies focused on anorexia where the disease is depicted as a way of achieving a successful life - those societies are the Internet fora commonly referred to as "pro-Ana".
Keywords: Ja cielesne; media społecznościowe; anoreksja; pro-ana; choroby cywilizacyjne; internet; porcelanowe motyle; body ego; social media; anorexia; diseases of affluence; porcelain butterflies